ANALISIS SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SUPPLIER KAIN DENGAN METODE ANALYTICAL HIERARCHY PROSES PADA CV NINA GORDYN - Efendi, Ferdian Edmund; Anwar, Septian (Kohesi: Jurnal Sains dan Teknologi, 2025)
In helping to determine the supplier of fabrics that can maintain reputation to consumers, of course CV. Nina Gordyn must implement a decision support system to avoid the possibility of fabric produced has a quality that is not in accordance with the company's standardization. The system used is Analythical Hierarvhy Proccess (AHP) where the results of this study are the most important criteria in the selection of suppliers by obtaining the percentage of 67%results, then the quantity criteria with a percentage of 23%, and finally the shipping criteria with a percentage of 10% For supplier priorities, namely PT. Three sons ranked first with a percentage of 9.50%, PT. Gizeo ranked second with a percentage of 9.35%, PT. Cendratex ranked third with a percentage of 9.24%, PT. Wijaya Sari to rank Keemapt with a percentage of 9.21%, PT. Idol Style ranked fifth with a percentage of 9.21%, PT. Vortex Inti Persada ranked sixth with a percentage of 9.03%, PT. Decco Garcia ranked seventh with a percentage of 8.93%, PT. Rejeki Ananda ranks eighth with a percentage of 8.69%, PT Hawila Indonesia ranks ninth with a percentage of 8.42% and PT. Three daughters ranked tenth with a percentage of 8.42%. So that the results of this study can help companies in the process of selecting suppliers of raw materials that are in accordance with standards